Cracking the Code: A Systematic Literature Review of Factors Influencing Micro Business Technological Innovation Adoption - Izhar Hafifi Zainal Abidin; Mohd Onn Rashdi Abd Patah; Mohd Aliff Abdul Majid; Samsul Bahri Usman (Information Management and Business Review, 2025)
Microbusinesses are essential in promoting local economies by creating job opportunities, generating income, and improving community welfare. Yet, their adoption of technological innovation remains limited due to various internal and external barriers, making the research on this topic continue to expand and remain relevant. This study systematically reviews existing literature to identify the key determinants influencing technological innovation adoption in microbusinesses. The findings reveal that internal factors, such as digital literacy, education levels, psychological traits, and access to technology, play a significant role in shaping their adoption decisions. Notably, knowledge and education emerge as critical enablers, as informed microbusiness owners demonstrate a higher propensity for technological innovation adoption. External influences, including perceived usefulness and ease of use of technological innovation and social influence, further impact the adoption process. Based on these findings, targeted training programs with mentorship initiatives and policy interventions like financial incentives are recommended to facilitate this population's adoption of technological innovation. As for academics looking to review this topic systematically, future studies are suggested to incorporate a broader range of databases and must not stop replicating to continuously update the literature to include the most recent studies.